Changes in one-carbon metabolism and DNA methylation in the hearts of mice exposed to space environment-relevant doses of oxygen ions (16O). (August 2019) - Miousse, Isabelle R.; Skinner, Charles M.; Sridharan, Vijayalakshmi; Seawright, John W.; Singh, Preeti; Landes, Reid D.; Cheema, Amrita K.; Hauer-Jensen, Martin; Boerma, Marjan; Koturbash, Igor
Highlights: Space-relevant doses of radiation lead to long-lasting changes in DNA methylation. Major satellites are particularly affected, at the methylation and expression levels. Transsulfuration of methionine is impacted at low dose. Abstract: Cardiovascular disease constitutes an important threat to humans after space missions beyond the Earth's magnetosphere. Epigenetic alterations have an important role in the etiology and pathogenesis of cardiovascular disease. Previous research in animal models has shown that protons and 56 Fe ions cause long-term changes in DNA methylation and expression of repetitive elements in the heart. However, astronauts will be exposed to a variety of ions, including the smaller fragmented products of heavy ions after they interact with the walls of the space craft. Here, we investigated the effects of 16 O on the cardiac methylome and one-carbon metabolism in male C57BL/6 J mice. Left ventricles were examined 14 and 90 days after exposure to space-relevant doses of 0.1, 0.25, or 1 Gy of 16 O (600 MeV/n). At 14 days, the two higher radiation doses elicited global DNA hypomethylation in the 5′-UTR of Long Interspersed Nuclear Elements 1 (LINE-1) compared to unirradiated, sham-treated mice, whereas specific LINE-1 elements exhibited hypermethylation at day 90. The pericentromeric major satellites were affected both at the DNA methylation and expression levels at the lowest radiation dose. DNA methylation was elevated, particularly after 90 days, while expression showed first a decrease followed by an increase in transcript abundance. Metabolomics analysis revealed that metabolites involved in homocysteine remethylation, central to DNA methylation, were unaffected by radiation, but the transsulfuration pathway was impacted after 90 days, with a large increase in cystathione levels at the lowest dose. In summary, we observed dynamic changes in the cardiac epigenome and metabolome three months after exposure to a single low dose of oxygen ions.